Comparison of Biomedical Variables in PCOS Patients with Normal Iranian Women. - Maryam Bagheri; Farnaz Sohrabvand; Mahnaz Lankarani; Zahra Zandieh; Fedyeh Haghollahi; Mamak Shariat (Tehran University of Medical Sciences, 2015)
Objective:To compared serum CRP levels and biochemical relation in PCOS patients with normal Iranian women. Materials and methods:This case-control study was performed on 52 individuals with PCOS (Rotterdam 2003 criteria). The cases were compared to 104 healthy non-PCOS, 20 to 35-year-old female subjects with no history of diabetes or renal diseases. Blood samples were taken on the 2(nd) to the 5(th) day of menstrual cycle for the evaluation of CRP levels, triglyceride, insulin, androstronedion, testestrone and total cholesterol. Results:The mean CRP was 1.38 (± 0.43) mg /dl in the PCOS group, and 1.08 (± 0.49) mg /dl (p= 0.240) in control group.High-Sensitivity C-Reactive Protein (HS-CRP) was positively correlated with the Body Mass Index (BMI) (r = 0.36, p= 0. 001). Before adjusting for age and BMI, CRP was correlated with LDL (r= 0.16, p= 0.03), total cholesterol (TC) (r= 0.17, p= 0. 03), Triglycerid (TG) (r= 0.23, p= 0.003), and the insulin (r= 0.20, p= 0. 01) notably in PCOS group. However, after adjustment was made for age and BMI, the correlation was attenuated in PCOS. The regression analyses depicted that CRP level was not under the influence of other medical parameters Conclusion: Conclusion:The results showed that mean CRP level was not significantly different between PCOs and normal women. After adjustment for age and BMI, CRP was not associated with any biochemical marker evaluated in this study. It seems that studied biochemical serum levels were mostly associated with obesity. So reduction of BMI may normalize the serum levels of CRP and other biochemical parameters.